Criterios de calidad en Didáctica de la Matemática - Recio, Tomás; González López, María José (Revista Complutense de Educación, 2007)
Some remarks are presented, concerning: 1. the generic difficulties arising in order to establish quality concepts and criteria in the realm of Mathematics Education, 2. the intrinsic difficulties to achieve this task within the Spanish socio academic context, 3. a catalog of tasks required to establish and to strengthen some quality parameters that might be of use, in particular, by the officers in charge of scientific evaluation. These issues are analyzed taking into consideration, as a reference, the case of Mathematical Sciences. The reasons for this choice are detailed and discussed in the document.